A history of autism conversations with the pioneers - Feinstein, Adam 1957-; Wiley InterScience (Online service). (Chichester, West Sussex, U.K. Malden, Mass. Wiley-Blackwell, 2010)
"This book explores the history of autism from the first descriptions of autistic-type behaviour to the present day. Through unprecedented interviews with many of the earliest pioneers in the field, and leading professionals working today across the world - including China, India, Russia and Latin America - A History of Autism casts fresh light on the way in which this disorder is, and has been, perceived and treated. Meticulously researched, the book draws on evidence from previously unpublished documents and illustrations, as well as the latest findings and case studies. In addition, interviews with parents of autistic children confirm the essential contribution they have made to a more profound understanding of this enigmatic condition"--Provided by publisher.
1. The Two Great Pioneers -- 2. The 1950s : The Seeds of Understanding -- 3. Blaming the Parents -- 4. The 1960s : The Parents Fight Back -- 5. The Two Teaching Pioneers -- 6. The 1970s : Major Steps Forward -- 7. Definition, Diagnosis, and Assessment : The History of the Tool -- 8. The 1980s and 1990s : Theories and Concepts -- 9. Autism in the Developing Nations -- 10. Where the Future Lies.
Electronic reproduction.
Keywords: Autism -- History; Electronic books